Racism and Its Effect in Freedom Writers Film by Richard La Gravense: Sociological Approach - Azna Yulinarni; Asridayani Asridayani; Dedi Efendi (Universitas Muara Bungo, 2020)
The purposes of the research are 1) to classify the types of racism that appear in “Freedom Writers” film. 2) to find the effects felt by the characters in the “Freedom Writer” film.In conducting this research, the writer uses descriptive qualitative method, which is a research method that finds fundamental answers about racism and types of racism and explains the effects caused by racism's actions on the character of players in the film using the sociological approach.From the results of this research, the writer found 21 data that divided into type and effect, there are data consist of racism that occur in Freedom Writer Films and they have been grouped based on their type based on Wilson's E Charles theory (2005), they are 10 data Overt/ Individual Racism and 6 data Institutional racism. The writer also finds three of the five fundamental effects of racism there are 5 data based on the theory of Allport (1991) they are Anticuotin, Discrimination and Physical attack.From all the data given, it can be concludes that Individual racism is mostly appear in the film, and then followed by Institutional Racism and some effects that found in Freedom Writers film. Key Words: Effect of Racism, Sociological, Freedom Writers